EVALUATION OF SMALL FAUNA SPECIES OF BIU WATERFALL, NIGERIAN ARMY UNIVERSITY, BORNO STATE - LAWAL , Muhammed Shittu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
This research was carried out to determine the relative abundance and distribution of small and micro fauna species in Biu waterfall couple with their physiochemical parameters in Nigeria Army University Campus. Research was done within three months. Data samples were taken via observation, use of different types of traps/nets, trap-camera and plankton nets at regular intervals. Laboratory analysis of the water and zooplankton species was carried in accordance with standard scientific method and taxonomy keys. Statistical tool used are t-Test and Standard Deviation at (0.05) using SPSS. Macrofauna species found are: Senila senilis), Portunidae, Pelusios spp, Grayia spp, and small fish (Tilapia zilli, Chrysichthys nigrodigitatus and Claria gariepinus). Other fauna are: Bufo regularis, Ostracods Eucypris virens, Lubricus spp and Sphaeridae. Macroinvertebrate insects were collected with highest value of abundance and distribution (48.7%) whereas Copecoda and Rotifer representing zooplankton had the least (2.7%). Also, intensive agrochemicals farming, active fishing and open waste dumping were observed. Monthly mean of Temperature (24.080C ± 0.23 - 27.00C ± 0.06), pH (7.32±0.04 – 8.49±0.26), Dissolved Oxygen (7.94±0.04 mg/l– 8.37±0.02 mg/l), respectively. These values falls within National recommended range. It is therefore suggested that extensive researches/networking with indigenes will improve use of aquatic ecosystem for conservation goals.